TIC 454140642: A Compact, Coplanar, Quadruple-lined Quadruple Star System Consisting of Two Eclipsing Binaries - Kostov, Veselin B.; Powell, Brian P.; Torres, Guillermo; Borkovits, Tamás; Rappaport, Saul A.; Tokovinin, Andrei; Zasche, Petr; Anderson, David; Barclay, Thomas; Berlind, Perry; Brown, Peyton; Calkins, Michael L.; et al. (Astrophysical Journal, 2021)
Abstract We report the discovery of a compact, coplanar, quadruple-lined, eclipsing quadruple star system from Transiting Exoplanet Survey Satellite data, TIC 454140642, also known as TYC 0074-01254-1. The target was first detected in Sector 5 with a 30-minute cadence in full-frame images and then observed in Sector 32 with a 2-minute cadence. The light curve exhibits two sets of primary and secondary eclipses with periods of P A = 13.624 days (binary A) and P B = 10.393 days (binary B). Analysis of archival and follow-up data shows clear eclipse-timing variations and divergent radial velocities, indicating dynamical interactions between the two binaries and confirming that they form a gravitationally bound quadruple system with a 2 + 2 hierarchy. The Aa+Ab binary, Ba+Bb binary, and A-B system are aligned with respect to each other within a fraction of a degree: the respective mutual orbital inclinations are 0.°25 (A versus B), 0.°37 (A versus A-B), and 0.°47 (B versus A-B). The A-B system has an orbital period of 432 days—the second shortest of the confirmed quadruple systems—and an orbital eccentricity of 0.3.